Computed tomography quantification of pulmonary vessels in chronic obstructive pulmonary disease as identified by 3D automated approach. Issue 40 (October 2016) - Yu, Nan; Wei, Xia; Li, Yan; Deng, Lei; Jin, Chen-wang; Guo, Youmin
Abstract : Abstract: The aim of this study was to investigate the vascular alteration of the whole lung and individual lobes in patients with COPD, and assess the association between pulmonary vessels and the extent and distribution of emphysema as well as pulmonary function by a 3-dimensional automated approach. A total of 83 computed tomography images from COPD patients were analyzed. Automated computerized approach was used to measure the total number of vessels at the fifth generation. The extent of emphysema (%LAA-950) in the whole lung and individual lobes were also calculated automatically. The association between the vascular number and the extent and distribution of emphysema, as well as the pulmonary function were assessed. Both the vascular number of fifth generation in the upper lobe and in the lower lobe were significantly negatively correlated with %LAA-950 ( P  < 0.05). Furthermore, there were significant, yet weak correlations between the vascular number and FEV1% predicted ( R  = 0.556, P  = 0.039) and FEV1/FVC ( R  = 0.538, P  = 0.047). In contrast, the vascular numbers were strongly correlated with DLco ( R  = 0.770, P  = 0.003). Finally, the vascular number correlated closer with %LAA-950 of upper lobes than with %LAA-950 of lower lobes. Pulmonary vessel alteration can be measured; it is related to the extent of emphysema rather than the distribution of emphysema.